Religious Messages Without Religion In Nas Daily Online Videos (Displacement Analysis in Authority) - Ahmad Assegaf (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
AbstractThe article tells about religious authority being taken over by content creators. The defeat of religious authorities arises because there are more and more people watching vlog videos than followers of religious authorities themselves. The link between video vlogs and religious authorities is video vlogs that accidentally take over the place or field of spreading religious knowledge. Observations were made through Facebook Nas Daily. This study uses Pauline Hope Cheong's Authority theory. In analyzing it, it is exactly the same as where Pauline hope Cheong explains his theory, namely through the four logics he considers to formulate the theory, namely disjucture and displacement as the formulation of the problem, and continuity and complementarity as solutions to problems. This research proves that religion is now not only obtained from religious authorities.Keywords: Authority, Nas Daily, Religious Authority, DisplacementAbstrakArtikel bercerita tentang otoritas keagamaan yang diambil alih oleh konten creator. kekalahan otoritas keagamaan muncul karena pengamat vidio vlog lebih banyak dan memiliki banyak kalangan daripada para pengikut dari otoritas keagmaan itu sendiri. Yang menghubungkan antara vlog video dengan otoritas keagamaan adalah video vlog yang tidak sengaja mengambil alih tempat atau lapangan penyebaran ilmu agama secara tidak sengaja. Pengamatan dilakukan melalui facebook Nas Daily. Penelitian ini menggunakan teori Authority milik Pauline Hope Cheong. Dalam mengalisisnya sama persis sebagai mana Pauline hope Cheong menenrangkan teorinya yaitu melalui empat logika yang dipertimbangkanya untuk merumuskan teori yaitu disjucture dan displacement sebagai perumusan problematika, dan continuity dan Complementarity sebagai solusi probelematika. Penelitian ini membuktikan bahwa agama sekarang tidak hanya di dapat dari otoritas keagamaan. Kata Kunci: Authority, Nas Daily, Otoritas Keagamaan, Displacement